Audrey, wait! - Benway, Robin (New York : Razorbill, 2008)
While trying to score a date with her cute co-worker at the Scooper Dooper, sixteen-year-old Audrey gains unwanted fame and celebrity status when her ex-boyfriend, a rock musician, records a breakup song about her that soars to the top of the Billboard charts.
Keywords: Dating (Social customs) -- Juvenile fiction; Fame -- Juvenile fiction; Bildungsromans